Heuristic Placement Routines For Two-Dimensional Rectangular Bin Packing Problems - Wong, Lily (2009)

(untitled)
In this study, we consider non-oriented and oriented cases of Two-Dimensional Rectangular Bin Packing Problems where a given set of small rectangles is packed without overlaps into a minimum number of identical large rectangles. In non-oriented case the rectangles are allowed to be rotated at 90° while the rectangles have fixed orientation in oriented case. We propose new heuristic placement routines called the Improved Lowest Gap Fill (LGFi) (for nonoriented case) and LGF